Social Science Education on Trust for an Active and Critical Citizenship - Sandahl, Johan; Micheletti, Michele; Verhaegen, Soetkin; Jansson, Maria; Johansson, Patrik (Stockholm University, 2025)
Student panel data from a project on trust. Conducted at two upper secondary schools 2021-2022.
Survey data from "Social Science Education on Trust for an Active and Critical Citizenship" (Swedish Research Council, 2019-03439_VR). https://www.vr.se/english/swecris.html#/project/2019-03439_VR .
Access to SurveyResponses file (in Swedish) on request after processing in accordance with Swedish Public Access to Information and Secrecy Act. File format .sav (SPSS) - can be opened with RStudio; also available as .csv (with potential minor file format conversion errors).

Paneldata från undersökning om tillit. Utförd på två gymnasieskolor 2021-2022.
Från forskningsprojektet "Vem kan man lita på? Samhällskunskapsundervisning om tillit för ett aktivt och kritiskt medborgarskap." (Vetenskapsrådet, 2019-03439_VR) . https://www.vr.se/swecris.html#/project/2019-03439_VR
SurveyResponses filen (på svenska) utlämnas på begäran efter prövning enligt OSL. Filformat .sav (SPSS) - kan öppnas i RStudio ; finns även som .csv (med ev. mindre konverteringsfel).
Samhällskunskapsundervisning om tillit för ett aktivt och kritiskt medborgarskap
Keywords: TEACHING PROFESSION; LÄRARPROFESSION; Higher and further education; Gymnasial och högre utbildning; Didactics; Didaktik; Political Science (Excluding Peace and Conflict Studies); Statsvetenskap (exklusive freds- och konfliktforskning)